Visible light irradiated photocatalytic activity of SnS2-CdS nanocomposite against the degradation of methyl orange dye. (16th April 2018) - Prabha, D.; Usharani, K.; Ilangovan, S.; Suganya, M.; Balamurugan, S.; Srivind, J.; Nagarethinam, V. S.; Balu, A. R.
Abstract: This paper reports the structural, morphological and photocatalytic properties of SnS2 nanopowder, CdS nanopowder and SnS2 -CdS nanocomposite synthesised by a cost effective chemical method. Diffraction peaks related to hexagonal SnS2 and CdS were observed in the XRD pattern of the composite. Nanosized grains were observed from the TEM image of the composite. The photocatalytic activity of the synthesised SnS2 -CdS nanocomposite was tested by the photodegradation of methyl orange (MO) under visible light and compared to that of pure SnS2 and CdS photocatalysts. The photocatalytic efficiency of the SnS2 -CdS composite after 150 min of light irradiation was found to be equal to 95·45% which is higher compared to that of pure SnS2 (74·09%) and CdS (80·24%) photocatalysts.